Genius and madness in the social representations of Mathematics teacher according to students and teachers (Práxis Educativa, 2011)
This paper presents an analysis of the social representations of 528 research participants, including 163 mathematics teachers and 365 students from state and private schools in Pernambuco, Brazil, about mathematics teachers The data collection was carried out using a three-phase methodology: free questionnaires, thematic seminars based on focus groups, and interviews. The results were progressively constructed with the participants, who in each research phase had feedback from the previous one. The data obtained from the questionnaires were subjected to a factor analysis using the Tri-deux software, whereas the data collected in the other two phases were analysed according to Bardin’s content analysis. The results revealed stereotypes such as the gift to teach and learn mathematics, and the superior and abnormal intelligence of mathematics teachers. Keywords: Social representations. Mathematics teacher. Stereotypes.